CSCP evaluator training guide to the selection and training of evaluators (Canadian Snowboard Federation, 2007)
This document provides guidelines about the following: • desirable characteristics of Evaluators, • suggestions for selecting Evaluators, and • the process of training and accrediting Evaluators.